Identificación de trazos alternativos: Carretera Lamas – Valle del Shanusi, empleando el método Aerofotogramétrico TOMO I - Rios Ruiz, Waldo Arturo (1994)
During many years has been need of build a Road East-West, that connect the rich valleys of the Shanusi, with peoples of the Interior of the province of Lamas. The present thesis work, reported the results in the identification of two alternative routes (I, II) for the purpose of tracing the road Shanusi Lamas-Valle, using the aerophotogrametric uprisings; i.e., the application of Photogrammetry to the topography, on the basis of aerial photographs, supplemented by satellite and on the basis of these images prepare the corresponding drawings. The aerophotogrametric uprisings are founded on the mathematical or graphical analysis of overlapping aerial photographs. Both routes are located between the square of weapons of the city of Lamas and the Center village of Alliance to the height of the kilometer 87 of it road Tarapoto-Yurimaguas, jurisdiction of the province of Lamas in the Department of San Martin.